The Decline of Polite Language in Educational Institutions - Effendy, Moh. Hafid; Munib, Abd; Rahman, Kholilur; Izzah, Ismatul (Universitas Muhammadiyah Malang, 2026)
The decline in politeness in educational institutions indicates a shift in social values ​​in students' communication practices, which are increasingly permissive of using offensive language as a form of self-expression or a symbol of group solidarity. This study aims to explore in depth the forms, causal factors, and efforts to revitalize politeness in secondary schools, highlighting the emergence of swearing and teasing as forms of verbal bullying that signal a decline in communication ethics. Using a qualitative-interpretive approach, data were collected through participant observation, semi-structured interviews, and documentation of students, teachers, and school administrators in several junior high schools in Waru District, Pamekasan. Analysis was conducted using the Dell Hymes SPEAKING model to explore the contextual dimensions of politeness and impoliteness. The results show that the decline in politeness is influenced by internal factors such as peer pressure, lack of habituation to polite language, and weak teacher role models. In contrast, external factors include social media influence, digital culture, and minimal family supervision. Revitalization efforts are carried out through polite speaking training, debate, language drama activities, and the integration of politeness values ​​into all school activities. This research confirms that politeness decadence is not merely a linguistic issue but a sociocultural phenomenon that demands systematic and sustainable character education intervention to build a culture of polite communication in educational environments.